XPS Investigation on Changes in UO2 Speciation following Exposure to Humidity. Issue 44 (27th April 2016) - Donald, Scott B.; Davisson, M. Lee; Nelson, Art J.
ABSTRACT: High purity UO2 powder samples were subjected to accelerated aging under controlled conditions with relative humidity ranging from 34% to 98%. Characterization of the chemical speciation of the products was accomplished using X-ray photoelectron spectroscopy (XPS). A shift to higher uranium oxidation states was found to be directly correlated to increased relative humidity exposure. Additionally, the relative abundance of O 2-, OH -, and H2 O was found to vary with exposure time. Thus, it is expected that uranium oxide materials exposed to high relative humidity conditions during processing and storage would display a similar increase in average uranium valence.